Emotional Intelligence and Leadership Style as Predictors of Conflict Management Skills: An Empirical Study of Educational Leaders - Arif Budi Raharjo; Nurul Aisyah (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: School principals often face conflicts that undermine school climate and educational effectiveness, particularly in Indonesian educational settings where diverse stakeholders have competing interests. This study aims to examine the contribution of emotional intelligence and leadership style to the conflict management skills of school principals, particularly within the context of educational leadership in Muhammadiyah secondary schools. Methodology: The study employed a quantitative approach with a cross-sectional design and utilized Structural Equation Modeling (SEM) to examine the direct relationships among variables. The measurement instruments included an emotional intelligence scale based on Goleman's model, a leadership style scale grounded in situational leadership theory, and a conflict management skills scale adapted from the Thomas–Kilmann model. Main Findings: The results indicated that emotional intelligence (β = 0.531, p < 0.001) and leadership style (β = 0.309, p = 0.013) significantly contributed to conflict management skills, with emotional intelligence emerging as the stronger predictor. The research model demonstrated good fit (CFI = 0.95; RMSEA = 0.05) and accounted for 44.4% of the variance in conflict management skills. These findings highlight the importance of developing emotional intelligence–based leadership integrated with adaptive leadership styles to enhance conflict management effectiveness. Novelty/Originality of this study: This study integrates the emotional intelligence model and situational leadership theory into a single conceptual framework, empirically tested within the Indonesian educational context, particularly in Muhammadiyah schools.